Skull Base Involvement by Acinic Cell Carcinoma of the Parotid Gland - Breen, Joseph T.; Carlson, Matthew L.; Link, Michael J.; Moore, Eric J.; Neff, Brian A.; Driscoll, Colin L.W. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objective Describe the clinical course and outcomes of patients with primary acinic cell carcinoma (ACC) of the parotid gland with skull base invasion or metastasis.Design Retrospective case series (1995–2011) at a single institution.Results Ten patients met study criteria. Mean and median time from initial diagnosis of parotid ACC to development of skull base disease were 14.6 and 10.2 years, respectively. Two patients demonstrated skull base disease on initial presentation. Those who pursued further treatment after developing disease at the skull base underwent surgery (4/7), stereotactic radiosurgery (4/7), or external beam radiation (3/7). The 10-year Kaplan-Meier estimated overall survival after initial diagnosis of parotid ACC was 80%. Once skull base invasion occurred, 2-year estimated overall survival was 50%.Conclusion Although primary ACC of the parotid generally caries an excellent prognosis, tumor control with cranial base disease is difficult and the majority of patients present with late aggressive recurrences. Our observations underscore the importance of long-term follow-up in this patient group.
Keywords: acinic cell carcinoma; salivary tumors; skull base; cranial base